Law Enforcement of Lactation Facilities and Their Relevance in Hindu Religious Teachings - Andriani, I Gusti Ayu Agung; Gunada, I Wayan Agus (Jurnal Penelitian Agama Hindu, 2025)
Lactation facilities in the public sector are a right for breastfeeding mothers, but the provision of proper facilities is still a major problem in Lombok. By regulation, public service sector managers must provide this facility optimally. Based on this, this study aims to analyze the factors that hinder law enforcement and its relationship with Hindu sacred teachings. The research uses an empirical juridical approach, and data is obtained through observation, interviews, and literature analysis. Based on the findings, the factors that cause the implementation of the policy to be not optimal include a lack of policy communication, limited resources, social stigma, and a lack of strict sanctions. Meanwhile, from the point of view of Hindu sacred teachings, the provision of lactation facilities is a form of implementation of the moral obligations that the government must carry out to the community, which is relevant in the teachings of dharma, sevanam, ahimsa, vasudaiva kutumbhakam, dana and karuna. It is important for the government to be firm in providing lactation facilities for breastfeeding mothers in the public service sector, not only as an implementation of regulations, but also as a moral obligation in implementing government duties according to religious teachings. Therefore, it will greatly support the government's efforts to support exclusive breastfeeding for breastfeeding mothers, and the findings are expected to be useful theoretically and practically in relevant studies in the future.